Tracing and characterization of foodborne botulism caused by the new MLST type Clostridium botulinum A2 in Hebei province, China - Lu, Ziwei; Feng, Jinzhi; Luo, Xia; Sun, Hui; Huang, Ying; Lu, Shuangshuang; Wang, Dai; Xu, Xuefang; Lu, Xuancheng; Xu, Lixia (Frontiers in Microbiology, 2025)
Foodborne botulism caused by botulinum neurotoxin (BoNT) remains an important form of botulism worldwide, with a high mortality rate and prolonged hospitalization time. Clostridium botulinum (C. botulinum) is the main microorganism responsible for producing BoNTs. This study reports a case of foodborne botulism caused by a C. botulinum subtype A2 strain from pickled eggs. We detected the BoNT gene using real-time PCR and the BoNT through the mouse bioassay (MBA) from both the patient’s feces and the pickled eggs and isolated C. botulinum A strains. The genetic SNP and phylogenetic tree analysis confirmed that the C. botulinum strains from the patient’s feces and the pickled eggs had the same origin. Although Hebei province is a high-incidence area for foodborne botulism, this is the first reported case of botulism caused by C. botulinum type A in pickled eggs in this region. The 10 isolated C. botulinum A strains all had a new ST193 type and contained the BoNT A toxin-producing gene and a potential virulence factor, GroEL. The BoNT A gene was classified as subtype A2 and belonged to the orfx cluster. The antibiotic resistance genes identified included cfr, spw, and vat. We also found that the genomic size of C. botulinum in the feces was smaller than that in the food and that most of the missing genes were related to desiccation/radiation resistance proteins, which might indicate gene loss during the process of entering the intestine. For this foodborne botulism outbreak, more emphasis should be placed on promoting food safety awareness among residents to prevent such botulism outbreaks in the future.